Electrocatalytic hydrogen evolution catalyst as well as preparation method and application thereof

By carrying out defect engineering and single-atom metal loading on the silene support, a highly dispersible single-atom catalyst is formed, which solves the problem of insufficient activity and stability of traditional catalysts and achieves efficient electrocatalytic hydrogen evolution reaction.

CN119433601APending Publication Date: 2025-02-14NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411568947.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional electrocatalytic hydrogen evolution catalysts have problems with insufficient activity and stability, and it is difficult to effectively control the structure and distribution of active sites, resulting in agglomeration of metal atoms, reducing atomic utilization, affecting catalytic activity, and leading to performance attenuation when the usage time increases.

Method used

Using defect-engineered silene carriers and single-atom metals loaded on their defect sites, specific defects are introduced through the biotemplate-quantum dot guidance method, and precise loading is used to form a single-atom metal precursor modified by biomolecules to form Highly dispersible single atomic catalyst.

Benefits of technology

The catalytic activity and selectivity of the catalyst are significantly improved, the activation energy of the hydrogen evolution reaction is reduced, the hydrogen generation rate is achieved, and a stable and efficient working state is maintained in the electrolyte with different pH values.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433601A_ABST
    Figure CN119433601A_ABST
Patent Text Reader

Abstract

The invention discloses an electro-catalytic hydrogen evolution catalyst and a preparation method and application thereof, and relates to the technical field of electro-catalysis, the electro-catalytic hydrogen evolution catalyst is composed of a silylene carrier subjected to defect engineering treatment and monatomic metal loaded on a defect site of the silylene carrier; according to the invention, defects are introduced into the carrier to preferentially load monatomic metal, and the monatomic metal and the carrier cooperate to increase active sites and improve the utilization rate of atoms; by means of the combination, monatomic metal loading can be more stable and uniform, agglomeration is reduced, the adsorption and desorption capacity on reactants can be enhanced, and the catalytic performance is improved. The combination of non-existing technologies such as a laser-induced plasma auxiliary technology and a biological template-quantum dot guide technology is realized, and the bottleneck that the activity and stability of a traditional catalyst are insufficient can be broken through.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalysis, and in particular to an electrocatalytic hydrogen evolution catalyst and a preparation method and application thereof. Background Art

[0002] Electrocatalytic hydrogen evolution catalyst is a key material for hydrogen production from water electrolysis. It can reduce the activation energy of hydrogen evolution reaction and increase the reaction rate. It is generally composed of a carrier with special properties (such as silicene) and active sites (such as single-atom metals such as iron, cobalt, and nickel), and can be used for hydrogen production from renewable energy and industrial hydrogen production.

[0003] In the field of electrocatalytic hydrogen evolution, traditional hydrogen evolution catalysts have many problems. Among them, insufficient activity and stability are one of the key problems. During the preparation process of traditional catalysts, it is difficult to effectively control the structure and distribution of active sites, which leads to easy agglomeration of metal atoms, reduces the number of active sites, reduces the atomic utilization rate, and thus affects the catalytic activity. Moreover, this agglomeration phenomenon and the instability of the active sites will further lead to the attenuation of catalyst performance as the use time increases. In addition, traditional defect introduction methods, such as thermal annealing or chemical etching, are difficult to accurately create defects at the atomic scale, and are prone to introduce impurities, affecting the performance of the catalyst. At the same time, the traditional single-atom loading method also has the problem of uneven distribution of metal atoms, and cannot give full play to the advantages of high atomic utilization and clear active sites of single-atom catalysts. These problems seriously limit the application effect and development of traditional hydrogen evolution catalysts in the fields of renewable energy hydrogen production and industrial hydrogen production. Therefore, there is an urgent need for a new electrocatalytic hydrogen evolution catalyst and its preparation method to improve the activity and stability of the catalyst and overcome the limitations of the prior art.

[0004] In view of this, an electrocatalytic hydrogen evolution catalyst and a preparation method and application thereof are provided to overcome the above problems. Summary of the invention

[0005] The object of the present invention is to provide an electrocatalytic hydrogen evolution catalyst and a preparation method and application thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides an electrocatalytic hydrogen evolution catalyst, which is composed of a silicene support treated with defect engineering and a single-atom metal supported on the defect sites of the silicene support;

[0007] Silicene carriers are two-dimensional materials with high specific surface area and excellent electron transport properties. After defect engineering treatment, there are various types of defects on their surfaces, including but not limited to vacancies and grain boundaries. The defects provide a special electronic structure and chemical environment for single-atom metals.

[0008] The single-atom metal is one or more transition metals selected from iron, cobalt, nickel, etc., and is dispersed at the defective positions of silicene at the atomic level. Each single-atom metal forms an independent active site to ensure that the catalyst has high atomic utilization and clear active sites.

[0009] A method for preparing an electrocatalytic hydrogen evolution catalyst comprises the steps of preparing a silicene carrier, introducing defects and loading single-atom metals.

[0010] Further, the silicene carrier preparation comprises the following steps:

[0011] Sapphire was used as the substrate and ultrasonically cleaned in acetone and ethanol solutions for 15-30 minutes to remove surface oil, dust and impurities. -8 In a high vacuum environment of mbar, annealing is performed at 800-1000℃ for 1-2 hours to make the atoms on the substrate surface arranged regularly, providing a high-quality nucleation surface for silicene growth;

[0012] In the molecular beam epitaxy equipment, high purity (>99.999%) silicon source is heated to <10 -10 mbar ultra-high vacuum environment, the silicon source temperature was adjusted to 1200-1500°C, and the beam intensity was controlled at 1×10 12 -1×10 13 atoms / cm 2 ·s, depositing a beam of silicon atoms on a pre-treated sapphire substrate;

[0013] After silicene growth is completed, the silicene film is carefully peeled off from the sapphire substrate by mechanical exfoliation to maintain the integrity of the film, which serves as a silicene carrier for the subsequent preparation of catalysts.

[0014] Further, the defect introduction includes the following steps:

[0015] A DNA molecule with a specific sequence design is selected as a biological template, and is dissolved in a Tris-HCl buffer solution with a pH of 7.2-7.6 to prepare a solution with a concentration of 1-3 mg / mL;

[0016] CdTe quantum dots with a particle size of 3-5 nm were prepared by hydrothermal synthesis;

[0017] The CdTe quantum dots and the DNA solution are mixed and stirred at room temperature for 1-2 hours to allow the two to form a quantum dot-DNA complex through electrostatic interaction and coordination bonds, and the molar ratio of the quantum dots to the DNA is controlled to be 1:10-1:30;

[0018] The stripped silicene film was immersed in a quantum dot-DNA complex solution and cultured at 30-35°C for 4-6 hours to allow the complex to adsorb on the silicene surface; then the solution was washed with water at a wavelength of 360-380nm and an intensity of 5-10mW / cm 2 The nanostructured silicene is irradiated with ultraviolet light for 2-4 hours to generate a local high-energy field in the quantum dots, inducing specific spatially distributed defects in silicene related to the DNA template sequence; finally, the DNA template is removed by electrophoresis (under appropriate electrophoresis buffer and an electric field of 10-20 V / cm).

[0019] Further, the single atom metal loading includes the following steps:

[0020] Using iron as a single-atom metal, a peptide chain containing a specific amino acid sequence (such as -arginine-cysteine-serine-) is designed and prepared by solid-phase synthesis or liquid-phase synthesis;

[0021] The peptide chain is reacted with ferric acetylacetonate (Fe(acac)3) in a mixed solution of ethanol and water (volume ratio of 3:1) to form a coordination bond between the cysteine ​​at one end of the peptide chain and the iron atom, thereby obtaining a biomolecule-modified iron precursor;

[0022] The defective silicene film is immersed in a biomolecule-modified iron precursor solution at a concentration of 0.05-0.1 mol / L and stirred at room temperature for 2-3 hours, so that the arginine and serine at the other end of the peptide chain can combine with the functional groups at the silicene defects (such as hydroxyl groups, silicon-hydrogen bonds, etc.) through hydrogen bonds and coordination bonds, and the iron atoms are precisely loaded at the defect positions to form single-atom catalysts.

[0023] Furthermore, during the growth process, the growth temperature is controlled at 700-900°C.

[0024] Furthermore, in the preparation of CdTe quantum dots with a particle size of 3-5 nm by the hydrothermal synthesis method, a tellurium source, a cadmium source, a reducing agent and a stabilizer are mixed in deionized water at a preset molar ratio to form a mixed solution, which is reacted in a high-pressure reactor at 150-200° C. for 12-24 hours, and the quantum dot solution is taken out after cooling to room temperature.

[0025] An application of an electrocatalytic hydrogen evolution catalyst is used in renewable energy hydrogen production and industrial hydrogen production.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The catalytic activity and selectivity of the catalyst are significantly improved by combining defect engineering in active site optimization with single-atom catalysts. In the hydrogen evolution reaction, the defects such as vacancies and grain boundaries produced by defect engineering on the silicene carrier provide a special electronic structure and chemical environment for the single-atom metal, allowing it to be dispersed at the defect position of silicene at the atomic level, and each single-atom metal becomes an independent active site. This combination allows the catalyst to efficiently catalyze the hydrogen evolution reaction in an acidic or alkaline electrolyte environment when a certain voltage is applied across the electrodes in a water electrolysis hydrogen production system. Compared with traditional hydrogen evolution catalysts, this catalyst can achieve a higher hydrogen production rate under the same voltage conditions.

[0028] There is a strong synergistic effect between the single-atom metal and the defects on the silicene carrier, which reduces the activation energy of the hydrogen evolution reaction. On the one hand, the special electronic structure and chemical environment at the defect create favorable conditions for the adsorption of hydrogen molecules and provide a large number of reaction starting sites; on the other hand, the electron cloud around the single-atom metal rearranges under the interaction with the defect, greatly enhancing the adsorption and desorption capacity of hydrogen, making the entire hydrogen evolution reaction easier.

[0029] Single metal atoms are dispersed at the atomic level in the defective positions of silicene, ensuring high atomic utilization and clear active sites of the catalyst. This high dispersion avoids the problem of reduced active sites and reduced utilization caused by metal agglomeration in traditional catalysts, giving full play to the advantages of single-atom catalysts, allowing each single metal atom to effectively participate in the catalytic reaction.

[0030] The catalyst can maintain a stable and efficient working state in electrolytes with different pH values, showing good adaptability to all pH values. This allows it to be used in various complex electrolysis environments, and can stably exert catalytic effects under both acidic and alkaline conditions, providing reliable technical support for renewable energy hydrogen production, industrial hydrogen production and other fields.

[0031] In terms of defect introduction, high-energy-density femtosecond laser pulses are focused on the surface of the carrier material, which can vaporize the material to form a plasma in a very short time, and then produce highly controllable defects, including vacancies, grain boundaries, and specific topological defects (such as skyrmions) during the expansion and cooling of the plasma. By precisely controlling the laser parameters, the type, density, and distribution of defects can be precisely controlled at the atomic scale without introducing impurities, which is impossible with traditional methods. In the single-atom loading link, within nanoseconds after laser treatment, the metal precursor is adsorbed and decomposed at the defect position of the carrier with the help of highly active free radicals and ions in the plasma, making the deposition of metal atoms at the defects highly selective and uniform, overcoming the problem of metal atom agglomeration in traditional wet chemical methods, while utilizing the unique electronic and chemical environment at the defect to achieve a perfect combination of single atoms and defects.

[0032] In terms of defect introduction, biological templates are used to guide the growth of carrier materials, and quantum dots are combined to generate local high-energy fields under light, inducing the carrier material to produce defects with specific spatial distributions. The biological templates can be easily removed without affecting the performance of the catalyst. When loading single atoms, single-atom metal precursors modified with biological molecules are used to accurately load single-atom metals at defect locations through biological molecule bridging. This method utilizes the high specificity and selectivity of biological molecules, providing a new way for the combination of single atoms and defects. At the same time, biological molecules can degrade themselves under mild conditions, and no residual impurities will affect the performance of the catalyst. This is also an effect that is difficult to achieve with traditional technologies.

[0033] Defects provide more favorable adsorption sites for single-atom metals, making the loading of single-atom metals more stable and uniform, and reducing agglomeration. This stable and uniform loading method not only ensures the high activity of single-atom catalysts, but also maintains the performance stability of the catalyst during long-term use, reduces performance degradation caused by agglomeration or changes in active sites, and further extends the service life of the catalyst, which is of great significance in practical industrial applications. At the same time, the regulatory effect of single-atom metals on the electronic structure around defects enhances the adsorption and desorption capacity of hydrogen. The virtuous cycle formed by this interaction significantly improves the overall performance of the catalyst more than expected, bringing new breakthroughs to the field of electrocatalytic hydrogen evolution and solving the problems of the insufficiency of traditional catalysts in terms of activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The schematic diagram is a schematic diagram of an electrocatalytic hydrogen evolution catalyst and a preparation method and application thereof of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] For example, see Figure 1 :

[0037] An electrocatalytic hydrogen evolution catalyst:

[0038] The electrocatalytic hydrogen evolution catalyst is mainly composed of a silicene carrier that has undergone defect engineering and a single-atom metal loaded on its defect sites.

[0039] As a two-dimensional material with high specific surface area and excellent electron transport performance, silicene is an ideal catalyst carrier. After defect engineering treatment, there are various types of defects such as vacancies and grain boundaries on the surface of silicene, which provide special electronic structures and chemical environments for the subsequent loading of single-atom metals.

[0040] Single metal atoms can be transition metals such as iron, cobalt, and nickel, which are dispersed at the defective positions of silicene at the atomic level. Each single metal atom becomes an independent active site, and this high dispersion ensures high atomic utilization and clear active sites of the catalyst.

[0041] A method for preparing an electrocatalytic hydrogen evolution catalyst: biological template-quantum dot guided preparation method:

[0042] (I) Preparation of silicene carrier

[0043] The following is a specific process for preparing silicene thin films as silicene carriers by molecular beam epitaxy (MBE) technology:

[0044] Substrate preparation:

[0045] First, a suitable substrate material is selected. In this embodiment, sapphire is selected as the substrate. The sapphire substrate is placed in acetone and ethanol solutions in turn and ultrasonically cleaned for 15-30 minutes each time to thoroughly remove oil, dust and other possible impurities on the surface.

[0046] After cleaning, place the sapphire substrate in a high vacuum environment (<10 -8 mbar), and annealing is performed at a high temperature of 800-1000°C for 1-2 hours. Through this process, small molecules adsorbed on the substrate surface can be further removed, and the atomic arrangement on the substrate surface can be more regular, providing a high-quality nucleation surface for the growth of silicene.

[0047] Silicene growth:

[0048] Using a high-purity silicon source (purity> 99.999%), the silicene growth operation is carried out in a molecular beam epitaxy device. The inside of the device is evacuated to an ultra-high vacuum environment (<10 -10 mbar) to ensure the purity of the growth environment and avoid interference of impurities on silicene growth.

[0049] The temperature of the silicon source is adjusted to be in the range of 1200-1500°C, and the beam intensity is precisely controlled (usually within 1×10 12 -1×10 13 atoms / cm 2 ·s), the silicon atom beam is stably deposited on the pre-treated sapphire substrate.

[0050] During the growth of silicene, the growth temperature needs to be optimized. After many experiments, it was found that when the growth temperature is maintained at 700-900°C, silicene can achieve better growth quality. In this embodiment, the growth temperature is set to 800°C. At this temperature, silicon atoms have a suitable mobility on the substrate and can be arranged in an orderly manner to form a high-quality silicene film.

[0051] The growth of silicene is determined by real-time monitoring of the reflection high-energy electron diffraction (RHEED) pattern. When the RHEED pattern shows clear, continuous and periodic diffraction stripes, it indicates that silicene is growing in a good crystalline state. Based on this monitoring result, the silicon source temperature, beam intensity and growth time and other parameters are adjusted in a timely manner to ensure that the silicene film can continue to grow stably to the required thickness and area.

[0052] Silicene film peeling:

[0053] After silicene is grown on the sapphire substrate, the silicene film is carefully peeled off from the substrate using a mechanical peeling method. During the peeling process, attention should be paid to the gentleness of the operation to avoid damage to the silicene film and ensure its integrity. The peeled silicene film is the silicene carrier required for the subsequent preparation of the catalyst, and it should be properly stored for future use.

[0054] (II) Defect introduction

[0055] Biological template and quantum dot preparation:

[0056] A specific DNA molecule is selected as a biological template, and its sequence is carefully designed to have a specific structure and function according to the type and distribution of defects to be induced. For example, the base sequence of the DNA molecule can be designed according to the expected spatial position of the target defect on the silicene surface, so that it can better combine with quantum dots and guide the generation of defects.

[0057] The designed DNA molecule was dissolved in a Tris-HCl buffer solution (pH=7.2-7.6), and a solution with a concentration of 1-3 mg / mL (2 mg / mL in this embodiment) was prepared by precise weighing and stirring.

[0058] CdTe quantum dots are prepared by hydrothermal synthesis. The specific steps are as follows: First, an appropriate amount of tellurium source (such as tellurium powder), cadmium source (such as cadmium chloride), and a suitable reducing agent (such as sodium borohydride) and stabilizer (such as mercaptoethanol) are mixed in deionized water in a certain molar ratio to form a uniform mixed solution. Then, the mixed solution is transferred to a high-pressure reactor and a hydrothermal reaction is carried out at a temperature of 150-200°C for 12-24 hours. Through this process, CdTe quantum dots with a particle size of 3-5nm (4nm in this embodiment) can be synthesized. After the reaction is completed, wait for the reactor to cool naturally to room temperature, take out the generated quantum dot solution and carry out subsequent treatment.

[0059] The synthesized CdTe quantum dots are mixed with the previously prepared DNA solution and stirred using a magnetic stirrer at room temperature for 1-2 hours (1.5 hours in this embodiment). During the stirring process, the quantum dots and DNA molecules are bound to each other through electrostatic effects and coordination bonds to form quantum dot-DNA complexes. By precisely controlling the amount of reactants, the molar ratio of quantum dots to DNA is maintained within the range of 1:10-1:30 (1:20 in this embodiment) to ensure the formation effect of the complex and the subsequent effectiveness of defect induction.

[0060] Defect Induction and Template Removal:

[0061] The peeled silicene film is immersed in the solution containing the quantum dot-DNA complex, and placed in a constant temperature shaking incubator for shaking culture at a temperature of 30-35° C. for 4-6 hours (5 hours in this embodiment). During this process, the quantum dot-DNA complex will gradually adsorb on the silicene surface.

[0062] After the adsorption is completed, the entire system is placed under a UV irradiation device and irradiated with a UV lamp with a wavelength of 360-380 nm (370 nm in this embodiment) and the irradiation intensity is set to 5-10 mW / cm 2 (In this embodiment, 8mW / cm 2), the irradiation time is 2-4 hours (3 hours in this embodiment). Under the irradiation of ultraviolet light, quantum dots absorb light energy and generate a local high energy field, which interacts with the surface of silicene, thereby inducing silicene to produce defects with a specific spatial distribution. The distribution of these defects is closely related to the sequence of the DNA template, because the DNA template has determined the distribution position of the quantum dots on the surface of silicene during the adsorption process, thereby indirectly determining the location of the defects.

[0063] After defect induction is completed, the DNA template needs to be removed from the system to avoid its impact on subsequent single-atom metal loading and catalyst performance. This embodiment uses an electrophoretic method to remove the DNA template. The specific operation is as follows: the solution containing the silicene film, quantum dots and residual DNA template is transferred to an electrophoresis tank, and electrophoresis is performed under suitable electrophoresis buffer (such as Tris-acetate buffer) and electric field conditions (generally the electric field strength is 10-20V / cm). Because the DNA molecule is charged, it will move in a specific direction under the action of the electric field, thereby separating from the silicene film and quantum dots, and finally achieving effective removal of the DNA template.

[0064] (III) Single Atom Metal Loading

[0065] Preparation of single-atom metal precursors modified with biomolecules:

[0066] Taking iron as a single-atom metal as an example, a peptide chain containing a specific amino acid sequence (such as -arginine-cysteine-serine-) is first designed. The peptide chain is prepared according to the designed amino acid sequence through conventional organic synthesis methods, such as solid phase synthesis or liquid phase synthesis.

[0067] The prepared peptide chain is reacted with ferric acetylacetonate (Fe(acac)3) in an ethanol-water mixed solution (volume ratio of 3:1). During the reaction, the cysteine ​​at one end of the peptide chain forms a stable complex with the iron atom through a coordination bond, thereby obtaining a biomolecule-modified iron precursor.

[0068] Single Atom Metal Load Operation:

[0069] The defective silicene film after defect induction treatment is immersed in the above-mentioned biomolecule-modified iron precursor solution (concentration is 0.05-0.1 mol / L, 0.08 mol / L in this embodiment), placed at room temperature, and stirred with a magnetic stirrer for 2-3 hours (2.5 hours in this embodiment).

[0070] During the stirring process, the arginine and serine at the other end of the peptide chain can combine with the functional groups (such as hydroxyl groups, silicon-hydrogen bonds, etc.) at the silicene defect through hydrogen bonds and coordination bonds, thereby accurately loading the iron atoms at the defect positions to form single-atom catalysts. Through this biomolecular bridging method, it is possible to ensure that the iron atoms are highly selectively and uniformly loaded at the silicene defect positions, providing good active sites for the subsequent catalytic hydrogen evolution reaction.

[0071] Application of an electrocatalytic hydrogen evolution catalyst:

[0072] The electrocatalytic hydrogen evolution catalyst exhibits excellent performance in the electrocatalytic hydrogen evolution reaction, which is mainly attributed to the ingenious combination of defect engineering in active site optimization and single-atom catalysts.

[0073] In the water electrolysis hydrogen production system, the prepared catalyst is evenly coated on the electrode surface, and the electrode can be made of common electrode materials such as graphite electrode or titanium electrode. When a certain voltage is applied to both ends of the electrode, the catalyst can efficiently catalyze the hydrogen evolution reaction in an acidic (such as 0.1 mol / L hydrochloric acid solution) or alkaline (such as 1 mol / L potassium hydroxide solution) electrolyte environment.

[0074] During the preparation of the catalyst, the defect engineering treatment of the silicene carrier provides extremely favorable adsorption sites for single-atom metals. For example, the defects such as vacancies and grain boundaries generated by the bio-template-quantum dot-guided method can enable single-atom metals (such as iron) to be loaded on silicene in a stable and uniform manner, effectively avoiding the occurrence of agglomeration. This highly dispersed state ensures that each single-atom metal can participate in the catalytic reaction as an independent active site, giving full play to the advantages of high atomic utilization and clear active sites of single-atom catalysts.

[0075] At the same time, the presence of single-atom metals has a positive regulatory effect on the electronic structure around the defects. In the process of hydrogen evolution reaction, for the reactant hydrogen, there is a strong synergistic effect between the defects on the silicene carrier and the single-atom metal. On the one hand, the special electronic structure and chemical environment at the defect create favorable conditions for the adsorption of hydrogen molecules and provide a large number of reaction starting sites; on the other hand, the electron cloud around the single-atom metal is rearranged under the interaction with the defects, greatly enhancing the adsorption and desorption capacity of hydrogen. This synergistic effect significantly improves the catalytic activity and selectivity of the catalyst and reduces the activation energy of the hydrogen evolution reaction. Compared with traditional hydrogen evolution catalysts, under the same voltage conditions, this catalyst can achieve a higher hydrogen production rate, and can maintain a stable and efficient working state in electrolytes with different pH values, showing good full pH adaptability, providing a highly innovative and promising solution for the field of electrocatalytic hydrogen evolution, and is expected to be widely used in renewable energy hydrogen production, industrial hydrogen production and other fields.

Claims

1. An electrocatalytic hydrogen evolution catalyst, characterized in that: It is composed of a silicene carrier that has been subjected to defect engineering and a single-atom metal loaded on the defect site of the silicene carrier; Silicene carriers are two-dimensional materials with high specific surface area and excellent electron transport properties. After defect engineering treatment, there are various types of defects on their surfaces, including but not limited to vacancies and grain boundaries. The defects provide a special electronic structure and chemical environment for single-atom metals. The single-atom metal is one or more transition metals selected from iron, cobalt, nickel, etc., and is dispersed at the defective positions of silicene at the atomic level. Each single-atom metal forms an independent active site to ensure that the catalyst has high atomic utilization and clear active sites.

2. A method for preparing an electrocatalytic hydrogen evolution catalyst, characterized in that: It includes silicene support preparation, defect introduction and single atom metal loading.

3. The method for preparing an electrocatalytic hydrogen evolution catalyst according to claim 2, characterized in that: The silicene support preparation includes the following steps: Sapphire was used as the substrate and ultrasonically cleaned in acetone and ethanol solutions for 15-30 minutes to remove surface oil, dust and impurities. -8 In a high vacuum environment of mbar, annealing is performed at 800-1000℃ for 1-2 hours to make the atoms on the substrate surface arranged regularly, providing a high-quality nucleation surface for silicene growth; In a molecular beam epitaxy device, a high purity (>99.999%) silicon source is heated to <10 -10 mbar ultra-high vacuum environment, adjust the silicon source temperature to 1200-1500℃, and control the beam intensity to 1×1012-1×10 13 atoms / cm 2 ·s, depositing a beam of silicon atoms on a pre-treated sapphire substrate; After silicene growth is completed, the silicene film is carefully peeled off from the sapphire substrate by mechanical exfoliation to maintain the integrity of the film, which serves as a silicene carrier for the subsequent preparation of catalysts.

4. The method for preparing an electrocatalytic hydrogen evolution catalyst according to claim 2, characterized in that: Defect introduction includes the following steps: A DNA molecule with a specific sequence design is selected as a biological template, and is dissolved in a Tris-HCl buffer solution with a pH of 7.2-7.6 to prepare a solution with a concentration of 1-3 mg / mL; CdTe quantum dots with a particle size of 3-5 nm were prepared by hydrothermal synthesis; The CdTe quantum dots and the DNA solution are mixed and stirred at room temperature for 1-2 hours to allow the two to form a quantum dot-DNA complex through electrostatic interaction and coordination bonds, and the molar ratio of the quantum dots to the DNA is controlled to be 1:10-1:30; The stripped silicene film was immersed in a quantum dot-DNA complex solution and cultured at 30-35°C for 4-6 hours to allow the complex to adsorb on the silicene surface; then the solution was washed with water at a wavelength of 360-380nm and an intensity of 5-10mW / cm 2 The nanostructured silicene was exposed to ultraviolet light for 2-4 hours, causing the quantum dots to generate a local high-energy field, inducing silicene to produce specific spatially distributed defects related to the DNA template sequence; finally, the DNA template was removed by electrophoresis.

5. The method for preparing an electrocatalytic hydrogen evolution catalyst according to claim 2, characterized in that: Single atom metal loading includes the following steps: Using iron as a single-atom metal, peptide chains containing specific amino acid sequences are designed and prepared by solid-phase synthesis or liquid-phase synthesis; The peptide chain was reacted with ferric acetylacetonate in ethanol- The reaction is carried out in a water mixed solution, so that the cysteine ​​at one end of the peptide chain forms a coordination bond with the iron atom, thereby obtaining a biomolecule-modified iron precursor; The defective silicene film was immersed in a 0.05- 0.1 mol / L biomolecule-modified iron precursor solution was stirred at room temperature for 2- 3 hours, the arginine and serine at the other end of the peptide chain combine with the functional groups at the silicene defect through hydrogen bonds and coordination bonds, and the iron atoms are precisely loaded at the defect position to form a single atom catalyst.

6. The method for preparing an electrocatalytic hydrogen evolution catalyst according to claim 3, characterized in that: During the growth process, the growth temperature is controlled at 700-900°C.

7. The method for preparing an electrocatalytic hydrogen evolution catalyst according to claim 4, characterized in that: The hydrothermal synthesis method was used to prepare particles with a diameter of 3- In the 5nm CdTe quantum dots, tellurium source, cadmium source, reducing agent and stabilizer are mixed in deionized water according to a preset molar ratio to form a mixed solution, which is reacted in a high-pressure reactor at 150-200℃ for 12- After 24 hours, the quantum dot solution was taken out after cooling to room temperature.

8. An application of an electrocatalytic hydrogen evolution catalyst, characterized in that: Used in hydrogen production from renewable energy and industrial hydrogen production.